Study of interrelations between Big Data and System Dynamics - Kiptikova, Alexandra; Pavlíček, Antonín, 1977-; Malinová, Ludmila; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
This master’s thesis focuses on interrelations between system dynamics and big data. The first part of the study reviews theoretical basis of system dynamics. The second part studies fundamentals of big data. The third, analytical part, studies approaches to the interrelations between system dynamics and big data.The master’s thesis aims to analyse the approaches to interconnecting system dynamics with big data. The main goal is achieved through the following sub-goals. The sub-goals of the study include researching system dynamics and big data separately, defining the approaches to interrelations between big data and system dynamics, and conducting an analysis of the above approaches. The analysis of the approaches to the interrelations between big data and system dynamics is performed in the following order. First, the logical models of each approach are designed. Second, the application scenarios for the approaches are suggested. Third, market potential of the above approaches is examined. Finally, a comparative study of the approaches is conducted. The results of the study are provided in the form of recommendations.The practical value of the study lies in the provision and analysis of different perspectives on the interrelations between big data and system dynamics. Currently, the amount of information on the issue is insufficient, and this paper aims to attract attention to the issue and to consider its significance for future development.
Vedoucí práce: Antonín Pavlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: informační management [obor dipl. práce]; diplomové práce; master's theses